Effects of four weeks of repeated sprint training on physiological indices in futsal players - Paulo Cesar do Nascimento; Ricardo Dantas De Lucas; Juliano Dal Pupo; Francimara Budal Arins; Carlo Castagna; Luiz Guilherme Antonacci Guglielmo (Universidade Federal de Santa Catarina, 2014)
The aim of this study was to investigate the effects of short repeated-sprint ability (RSA) training on the neuromuscular and physiological indices in U17 futsal players during the competitive period. Fourteen players were divided into two groups: intervention group (n = 8) and control group (n = 6). Both groups performed a repeated maximal sprint test (40-m MST), intermittent shuttle-running test (Carminatti's test) and vertical jumps before and after the training period. The intervention group was submitted to an additional four-week repeated sprints program, twice a week, while the control group maintained their normal training routine. There was no significant interaction between time and groups for all variables analysed (p > 0.05). However, a significant main effect was observed for time (p < 0.01) indicating an increase on speed at heart rate deflection point (VHRDP) and the continuous jump performance while the peak lactate (40m-LACpeak) and sprint decrement decreased after training, in both groups. Still, based on effect sizes (ES) the greater changes with practical relevance were verified for intervention group in important variables such as peak velocity (ES = 0,71), VHRDP (ES = 0,83) and 40m-LACpeak (ES = 1,00). This study showed that RSA-based and normal training routine are equally effective in producing changes in the analysed variables during a short period of intervention. However, the effect size suggests that four weeks of RSA training would be a minimum time that could induce the first changes of futsal player's physical fitness.